Pengaruh risiko kepatuhan, risiko operasional, dan likuiditas terhadap good corporate governance : studi kasus pada bank muamalat indonesia - Rosita, Halimatu (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the impact of compliance risk, operational risk, and liquidity on the implementation of Good Corporate Governance (GCG) at Bank Muamalat Indonesia. This study uses a quantitative approach, utilizing secondary data obtained from the company’s financial statements and annual reports. The data analysis technique used is multiple linear regression to examine the relationship between the independent and dependent variables. The results of the study indicate that compliance risk has a significant impact on GCG, reflecting the importance of regulatory compliance in improving the quality of corporate governance. Operational risk also impacts GCG, particularly in terms of efficiency and internal control. Meanwhile, liquidity plays a role in maintaining a company’s financial stability and enhancing stakeholder trust, although its impact on GCG can vary depending on the bank’s internal conditions. This study contributes to the growing body of literature on the relationship between risk management and corporate governance, particularly in Islamic banking. Furthermore, the results are expected to serve as a basis for bank management in formulating strategic policies to sustainably improve the quality of GCG implementation.